EFFECTS OF EXAMINATION MALPRACTICES ON STUDENTS FUTURE, CASE OF HIGHER TECHNICAL TEACHERS TRAINING COLLEGE, BAMBILI-BAMENDA - Nganchi, Kebuya Nathaniel; Charlotte, Mekongtso Ngwemezon (African Journal of Education and Practice, 2020)
Purpose: This study was necessitated by the fact that the researchers noticed so many mishaps during their final exams, amongst which was that many students were moving up and down in the exam hall, students identification papers were not checked upon entering the exam hall nor when they were writing, students going out after receiving their question papers without any invigilator accompanying them and thus it sought to examine the effects of examination malpractice on student's future. It made use of four research objectives which are; To examine the relationship between impersonation on students' future, to find out the effects of bribery on students' future, to evaluate the effects of intimidation on students future, and to propose possible solutions to curbing examination malpractice. Methodology: the Behavioural theory of Operant Conditioning by B.F Skinner and Social Learning Theory by Albert Bandura were used. The research design was a survey, and questionnaire was used to get respondents' opinions. Analysis was done using simple percentage count. Test was carried out using 120 respondents as the sample. Finding: the results revealed that impersonation is negatively related to student's future, bribery is negatively related to student's future, and intimidation is negatively related to student's future. From the objectives, we see that there is a relationship between cheating, impersonification, and exam malpractices as well as the fact that cheating during exams affects students future. Amongst the many recommendations, one of them was that the government through the Ministry of Higher Education (MINESUP) should integrate examination malpractices in the school curriculum as one of the cross cutting issues in the institutions of learning in order to enhance continuous awareness among learners.